Aktiveringens inverkan på unga hundars hull i Sverige : en enkätstudie - Ström, Linnéa (SLU/Dept. of Animal Environment and Health (until 231231), 2023)
Today, the dog (Canis lupus familiaris) is a common companion animal all over the world and there are currently 1 100 000 registered dogs in Sweden. Globally we currently have a growing problem with obesity in both humans and animals. Many dogs live a life closely linked to humans, which means that their routines are mainly controlled by humans. As obesity has become a growing prob-lem in the human population, it has also become a bigger problem in the world´s dog population. Overweight has been observed in more than half of the developed countries dog population. More-over, it has been reported that dog owners often underestimate the body condition score on their own dog. One factor that affect the increased frequency of the overweight dogs is that large parts of their daily lives are spent sedentary. In many other studies have found a connection between physical activity and dogs’ BCS. Another factor that affects the BCS is the design of feeding and activation routines. Since overweight in dogs is associated with several diseases that reduces the affected individual’s life quality and lifespan, it is important to investigate the causes of overweight. This study has reviewed surveys from the “Life with my Dog” project conducted at the Swedish University of Agricultural Sciences (SLU). The purpose of this study was to investigate whether there was any correlation between physical activity and BCS in young dogs in Sweden. The aim was also to investigate whether there was any correlation between dog owners’ visual estimation of the dogs’ body condition score based on images and the palpable assessment made by the dog own-ers. The results showed that only a small proportion of the dogs included were overweight at the age of 13 months. Moreover, the owners’ palpable BCS corresponded well with their BCS based on image comparisons. The results also showed that the physical activities’ type and amount partly had an impact on the young dogs’ BCS. The dogs that were reported as having a higher energy level at 12 months ...